IMPLEMENTASI ALGORITMA ENKRIPSI RSA PADA APLIKASI INSTANT MESSAGING - Ardiansyah Sukma Wijaya; Dodon T. Nugrahadi; Muhammad Itqan Mazdadi; Andi Farmadi; Ahmad Rusadi (Fakultas MIPA Universitas Lambung Mangkurat, 2020)
At this time the use of instant messaging applications is increasingly used compared to the use of SMS or other media because of its use which is more practical and faster. From the other side, the message information sent certainly requires confidentiality so that the message is not spread and known by others. For this reason mechanisms are needed, one of which is encryption to maintain message security. This research will implement the RSA (Rivest Shamir Adleman) encryption algorithm in the instant messaging application. This study uses a key length scenario of RSA 1024, 2048, 4096, and 6144 bits and a message length of 125, 250, 500, and 1000 characters implemented on 3 different devices. The results of testing on time and speed are the shorter the key used, the process will be shorter and faster. Keywords : RSA, Processing Time, Processing Speed